Engaging and Sustaining Adolescents in Community-Based Participatory Research. Issue 1 (January 2015) - LoIacono Merves, Marni; Rodgers, Caryn R.R.; Silver, Ellen Johnson; Sclafane, Jamie Heather; Bauman, Laurie J.
<x xml:space="preserve">Abstract</x> Community-Based Participatory Research partnerships typically do not include adolescents as full community partners. However, partnering with adolescents can enhance the success and sustainability of adolescent health interventions. We partnered with adolescents to address health disparities in a low-income urban community. In partnering with youth, it is important to consider their developmental stage and needs to better engage and sustain their involvement. We also learned the value of a Youth Development framework and intentionally structuring a youth-friendly Community-Based Participatory Research environment. Finally, we will raise some ethical responsibilities to consider when working with youth partners.